Cross-cultural adaptation and psychometric properties of the short version of COPSOQ II-Brazil - Gonçalves, Josiane Sotrate; Moriguchi, Cristiane Shinohara; Chaves, Thaís Cristina; Sato, Tatiana de Oliveira (Revista de Saúde Pública, 2021)
OBJECTIVES Translate and culturally adapt the short version of Copenhagen Psychosocial Questionnaire II (COPSOQ II) into Brazilian Portuguese (COPSOQ II-Br) and evaluate its psychometric properties. METHODS Translation and cultural adaptation followed the standardized guidelines. Structural validity was assessed using exploratory factorial analysis. Test-retest reliability was evaluated by intraclass correlation coefficient (ICC3,1) and internal consistency by Cronbach’s alpha. Floor and ceiling effect was considered acceptable if less than 15% of participants reported the lowest or highest scores. Measurement error was assessed by standard error of measurement (SEM), while construct validity was tested by correlating the COPSOQ II-Br, the Job Content Questionnaire and the Nordic Musculoskeletal Questionnaire. RESULTS The study evaluated a total of 211 civil servants and service providers in the test and 157 in the retest. After cross-cultural adaptation, the COPSOQ II-Br structure comprised seven domains and 11 dimensions. Most dimensions showed acceptable floor and ceiling effects, excepting “Work family conflicts” (floor effect of 26.1%), and “Meaning and commitment” and “Job satisfaction,” with ceiling floor of 27.5% and 22.3%, respectively. Cronbach’s alpha values reached the recommended levels (varied between 0.70 and 0.87). Test-retest reliability indicated that all dimensions had ICC between 0.71 and 0.81. SEM ranged from 0.6 to 2.2 and the construct validity showed good results with the tested instruments (significant positive and negative correlations). CONCLUSIONS All psychometric properties of the short version COPSOQ II-Br are suitable for use in Brazil. The instrument is thus validated and can be used by occupational health and human resources professionals to evaluate psychosocial working conditions.